ENGLISH AND INDONESIAN GREETINGS AS ADJACENCY PAIRS: A PRAGMATIC STUDY - Arni Arsyad Sultan (Elite : English and Literature Journal, 2020)
A speaker customarily opens the conversation by saying greeting to his or her interlocutor. At a glance, greetings maybe not a complicated activity but for the most part, they are highly conventionalized and follow patterned routines. Despite it, the pattern or sequence of greetings along with its type is dynamic and developed. The research aimed to describe the kinds of verbal and non-verbal greetings customarily shown in every exchange, to reveal the sequence of English and Indonesian greetings as adjacency pairs in social exchange. The data consists of English collected from "Twelve Years a Slave" while Indonesian data are obtained from observation, record, and field notes. Both of the data are analyzed by using descriptive qualitative method. The result of this research indicates that there are four types of Indonesian sequential greetings uncovered by Firth's theory, characterized by interjection-question, question-body language, interjection-invitation, and invitation. Each is used in a single utterance for each pair. Second, English data indicate the sequences of greetings uttered by first pair and second are symmetrical, body language preceding question, and body language, on the other hand, Indonesian greeting sequence, the researcher finds an asymmetrical pattern, question preceding question, body language, and visual response. Miscellaneous greeting sequences also appeared in both such as affirmation and facial expression, question and affirmation, affirmation and invitation, invitation and affirmation, and also question and direct answer.